Incisional hernia following ovariohysterectomy in a mixed-breed domestic cat - Anggieta Ratuyustiarany; Muhammad Farid Rizal; Hadrianus Lau; Donna Marie Leo; Hilma Lutfiah Sudarsyah; Rahmadhani Angger Syahputra; Reinier Melvern (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2025)
An incisional hernia is a postoperative complication that arises when the abdominal wall fails to achieve adequate closure following surgery, allowing abdominal tissues or organs to protrude through the incision site. This report describes a case of incisional hernia in a 3.4-kg female cat that developed an abdominal mass one month after ovariohysterectomy. Diagnosis was established based on a thorough physical examination of the patient. Surgical management consisted of repositioning the herniated tissue and layered closure of the abdominal wall. Postoperative care included the administration of antibiotics and analgesics to prevent infection and to manage pain. Clinical evaluation on postoperative day 7 revealed complete wound healing without complications, indicating favorable outcomes.